2019
DOI: 10.1101/571968
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Autologous adipose-derived stem cell transplantation enhances healing of wound with exposed bone in a rat model

Abstract: 18Objectives. Soft tissue wounds with exposed bone often require extended healing times 19 and can be associated with severe complications. We describe the ability of artificial 20 dermis with autogenic adipose-derived stem cells (ADSCs) to promote the healing of 21 wounds with exposed bone in a rat model. 22Methods. Adipose tissues harvested from the bilateral inguinal regions of Wistar rats 23 were used as ADSCs. Rats were randomly divided into control and ADSC groups to 24 investigate the efficacy of ADS… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
0
6
0
1
Order By: Relevance
“…One limitation of using ADSCs as a delivery vehicle for antibiotics is that their ability to do so is dependent on cell viability and integration at the injection site. By using DiI staining of ADSCs, a previous study showed that numerous ADSCs were distributed throughout granulation tissue up to 21 days post-transplantation 13 . We did not study cell viability and distribution after injection, which requires further study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One limitation of using ADSCs as a delivery vehicle for antibiotics is that their ability to do so is dependent on cell viability and integration at the injection site. By using DiI staining of ADSCs, a previous study showed that numerous ADSCs were distributed throughout granulation tissue up to 21 days post-transplantation 13 . We did not study cell viability and distribution after injection, which requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…ADSC and BMSCs for in vitro experiments were isolated from 20 9-week-old female Wistar rats (Japan SLC Co., Shizuoka, Japan). ADSCs were prepared as previously reported 13 , with modification. BMSCs were isolated from the same rats, as previously reported 51 , with modifications in the protocol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hamada et al (3) , comparing artificial dermis with adipose-derived stem cells in wounds with exposed bone in a rat model, reported that adipose-derived stem cells showed significantly higher expression of basic fibroblast growth factor (bFGF) and vascular endothelial growth factor (VEGF), thereby exhibiting potential for differentiation into fibroblasts and blood vessel endothelial cells.…”
Section: Regenerative Properties Of Adipose-derived Stem Cellsmentioning
confidence: 99%
“…The successful use of adipose-derived stromal/stem cells has been reported in aesthetic, cardiac, and reconstructive posttraumatic procedures (2) . Potential advantages of autologous fat grafting include abundant fat, easy harvesting via liposuction, and cost-effectiveness compared to commercially available artificial skin (3) .…”
Section: Introductionmentioning
confidence: 99%